Novel Biallelic Variant in the BRAT1 Gene Caused Nonprogressive Cerebellar Ataxia Syndrome - Qi, Yiming; Ji, Xueqi; Ding, Hongke; Liu, Ling; Zhang, Yan; Yin, Aihua (Frontiers in Genetics, 2022)
Recessive mutations in BRAT1 cause lethal neonatal rigidity and multifocal seizure syndrome (RMFSL), a phenotype characterized by neonatal microcephaly, hypertonia, and refractory epilepsy with premature death. Recently, attenuated disease variants have been described, suggesting that a wider clinical spectrum of BRAT1-associated neurodegeneration exists than was previously thought. Here we reported a ten-year-old girl with severe intellectual disability, rigidity, ataxia or dyspraxia, and cerebellar atrophy on brain MRI; two BRAT1 variants in the trans configuration [c.1014A>C (p.Pro338=); c.706delC (p.Leu236Cysfs*5)] were detected using whole-exome sequencing. RNA-seq confirmed significantly decreased BRAT1 transcript levels in the presence of the variant, further, it revealed an intron retention between exon 7 and exon 8 caused by the synonymous base substitute. Subsequent prenatal diagnosis for these two variants guided the parents to reproduce. We expand the phenotypic spectrum of BRAT1-associated disorders by first reporting the pathogenic synonymous variant of BRAT1 gene resulting in clinical severity that is mild compared to the severe phenotype seen in RMFSL. Making an accurate diagnosis and prognostic evaluation of BRAT1-associated neurodegeneration is important for reproductive consultation and disease management.